(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
This study aimed to observe the morphometric growth of Padina australis algae naturally in waters. The growth seen was the length, diameter and weight of the P. australis thallus in nature. Padina australis lives on a substrate in the form of sand, sandy gravel. Sampling by purposive sampling. Each individual sample clump was measured thallus morphology, namely; thallus length, thallus diameter, and mass weight (BM) and water quality measurements, including temperature, salinity, depth and tides were measured to see the impact on the growth of P. australis. Toduku Island, Kec. South Jailolo, West Halmahera Regency, is the location for research on the growth of the Padina australis algae. Results; The length and diameter of the thallus had the highest mean value at the ST.I location and the lowest at ST.II, from the results of the analysis of the variance, it showed that the growth of the Padina australis thallus length and weight was not significantly different or non-significant with the Fhit value < Ftable for each Fhit length (2 .29) and Fhit weight (-16.52) < Ftab (3.54) while the thallus diameter showed a significant value, namely Fhit (14.62) > Ftab (3.54) at 95% confidence. Of the three parameters, only the thallus diameter showed a significant relationship with water quality conditions at the study site and was still significant for seaweed growth, while the relationship between thallus length and weight with water quality parameters (temperature, salinity, pH, etc.) significant.